Psychophysiological and stress responses to competition in team sport coaches: An exploratory study. Issue 5 (13th May 2013) - Hudson, J.; Davison, G.; Robinson, P.
Abstract : Examinations of stress in coaches have mainly been qualitative and focused on chronic stressors. This exploratory study examined stress responses in coaches during competition, including psychological and physiological indices. Using reversal theory, we examined metamotivational state profiles during competition. Ten male team sport coaches (mean age 39.8 ± 13.12 years) reported levels of subjective stress, pleasant and unpleasant emotions, metamotivational state, and provided saliva samples, on a competition day: 15 min prior to the pre‐match team talk; start of the match; end of the first half; start of the second half, and end of the match, then at equivalent times on a noncompetition day. Saliva samples were assayed for alpha‐amylase activity. On competition day, alpha‐amylase activity was significantly higher, as were subjective stress, arousal, and unpleasant emotions. Prior to and during active play, participants were mainly in the conformist, alloic (other‐oriented), and mastery states, and at the end of the match, in the telic and sympathy states. Only 22 metamotivational state reversals were observed, mostly at the start and end of the match. The elevated levels of subjective stress, alpha‐amylase activity, and unpleasant emotions suggest that educational programs may be useful for some coaches to manage psychological states during competition.